Multiparametric CT-based assessment of pretracheal anatomical relationships for safe tracheotomy: A long-forgotten issue revisited. (March 2022) - Zhu, Dan; Abdelrehem, Ahmed; Wu, Lizhong; Xia, Ronghui; Zhu, Yaxin; Sheng, Surui; Ai, Songtao; Ma, Chunyue
Abstract: Objectives: To assess the anatomical relationships and variations in the pretracheal space and to guide tracheotomy procedures in a safe manner with image-based evidence. Materials and methods: A retrospective study was conducted on unirradiated patients requiring elective tracheotomies. Preoperative contrast-enhanced CT (CECT)/CT venography (CTV) was applied for an anatomical evaluation of the pretracheal region. Vascular morphologies were compared for three vessels: the anterior jugular vein (AJV), the innominate artery (IA) and the inferior thyroid vascular plexus (ITVP). The relationships between the thyroid isthmus and the 2nd–4th tracheal rings were also analyzed. Results: A total of 120 patients were identified, most of whom (n = 110, 91.7%) had head and neck squamous cell carcinomas. Patients with recognizable AJVs (n = 118) were divided into 3 groups: single-branch (n = 11, 9.2%), double-branch (n = 105, 87.5%), and multibranch (n = 2, 1.7%). In addition, IAs were categorized as low-bifurcation (n = 51, 42.5%), high-bifurcation (n = 40, 33.3%), platform (n = 27, 22.5%) and variant types (n = 2, 1.7%). Within the platform types, high-lying IAs (n = 15, 8.3%) might have interfered with the standard tracheal incisions due to possible IA-tracheal overlay. This interference was also related to the height of intraoperative tracheal incisions (rn = 0.364, P = 0.001). Within ITVPs, independent-trunk types were found in 71 cases (59.2%), while common-trunk types were found in 45 (37.5%). In addition, a low thyroid isthmus (suprasternal-isthmus distance <3 cm) was found in 83 cases (69.2%). Conclusions: CT image-based evidence can prepare junior practitioners with important pretracheal anatomical information, thereby facilitating safer tracheotomy procedures. Our results shed light on vascular relationships for emergent tracheotomy.